The impact of using software technologies in construction industries safety / Awang Muzareeq Syazani Awang Moslem - Awang Moslem, Awang Muzareeq Syazani (2021)
There has been number of study and research conducted concerning the safety issues and management in the construction sector. We all know that the construction sector is a high-risk industry. This paper will identify the problems and challenges faced in implementing software technologies in the constructions safety. There are a few problems that has been identified which is lack of communications, the attitude of labourers and the safety procedures are taken very lightly on site by the employers and employees. The aim of this paper is to study the challenges and barriers of implementing software in safety management inside the construction industry and ways to solve it. The research has three objectives: to determine the importance of software programmes in construction safety, to identify the barriers to using software as a medium for safety in the construction sector, and to offer solutions for using software as a medium for safety in the construction sector. This study used a quantitative methodology, which included a questionnaire survey, and the data was analysed using SPSS software. The barriers in implementing software for safety are high cost of implementation, high cost for installation, lack of knowledge on software, lack of technology advancement and lack of awareness in technology utility in the industry. The strategies in promoting software are subsidizing price of software, offer free safety training and government providing incentives for the software. The selected respondents for this research is the companies specialized in building that are involved in the construction sector in Sarawak. The data has been collected through questionnaires that are distributed to 108 companies. Data analysis and a literature evaluation were used to meet the research's goals and objectives.